Delivering oral surgery training in a primary care clinic. (2nd October 2015) - Nair, P.; Ross‐Russell, M.
Abstract: Aim: To describe the Cambridgeshire Community Services NHS Trust Dental Service's experience of the oral surgery training of two general dental practitioners (GDPs). Materials and methods: Cambridgeshire Community Services NHS Trust Dental Service has previously presented the results of a 12‐month clinical attachment to develop the skills of a referring general dental practitioner in oral surgery. We now describe our experience of further oral surgery training of two general dental practitioners who benefitted from a 6‐month programme. This included one half day per week of "hands on" oral surgery experience and the development of a portfolio of evidence to demonstrate competence. Results: Our results led us to conclude that a 6‐month training programme in a primary care clinic can develop trainees with appropriate skills to safely provide the full range of oral surgical treatment that is appropriate to deliver in a primary care setting. Conclusion: GDPs can be taken from low confidence and over referral to high confidence, low referral rate and the ability to take a lead in this area of clinical dentistry within their own practices. We would like Health Education England/LETBs to consider training in primary care when planning oral surgical training at all levels.